Validation of the Living Kidney Donor Profile Index in a European cohort and comparison of long-term outcomes with US results. Issue 6 (9th May 2018) - Rehse, Gregor; Halleck, Fabian; Khadzhynov, Dmytro; Lehner, Lukas J; Kleinsteuber, Anna; Staeck, Anja; Duerr, Michael; Budde, Klemens; Staeck, Oliver
Abstract: Background: Recently, a risk index for living donor kidney (LDK) transplantation [living kidney donor profile index (LKDPI)] was proposed to compare LDKs with each other and with deceased donor kidneys (DDKs). Until now, the LKDPI has not been validated externally. Methods: This long-term retrospective analysis included 1305 consecutive adult kidney transplant recipients who were transplanted 2000–16 in our centre. The Kidney Donor Profile Index (KDPI) was calculated in 889 DDKs and the LKDPI in 416 LDKs. Outcome was followed over a median of 6.5 years. Results: The median LKDPI was 17 and the median KDPI was 69, with a high proportion of donor kidneys with a very high KDPI (40% KDPI ≥ 80). Categorization of LDK into LKDPI quartiles (LKDPI −45–3, 3–17, 17–33, 33–90) revealed a significant difference in death-censored graft survival. Comparing corresponding subgroups of the LKDPI and KDPI (LKDPI/KDPI 0–20 or 20–40) showed comparable graft survival. A multivariate analysis adjusting for relevant recipient factors revealed the KDPI [hazard ratio (HR) 1.21; P < 0.001) and LKDPI (HR 1.15; P = 0.049) as significant independent predictors of graft loss. Time-to-event receiver operating characteristic analyses for graft survival demonstrated lower predictive discrimination of the LKDPI [area under the curve (AUC) 0.55] compared with the KDPI (AUC 0.66). The 10-year graft survival of LDK recipients was inferior in the USA compared with our centre (79% versus 84%). Conclusions: These results provide external validation of the LKDPI to predict death-censored graft survival and confirm comparability of the LKDPI with the KDPI to discriminate post-transplant outcome.